GENETIC GAINS OF MILK YIELD AND MILK COMPOSITION AS REALIZED RESPONSE TO DAIRY COW SELECTION IN BBPTU-HPT BATURRADEN, INDONESIA - Rahayu, A. P.; Johari, S.; Kurnianto, E. (Diponegoro University, 2015)
The aims of this study were to estimate the heritabilities, examine the effects of dairy femaleselection and calculate the genetic gains on milk yield and milk composition in Baturraden Dairy CattleBreeding and Forage Centre (Balai Besar Perbibitan Ternak Unggul dan Hijauan Pakan Ternak /BBPTU–HPT Baturraden), Indonesia. The first lactation records of 221 dairy cows from 2006 to 2014were used. Heritabilities were estimated by paternal half-sib correlation. Comparison of averageperformances between daughter population (Ā) and initial dam population before selection ( ) wereconducted by Z-test. Annual genetic gain was calculated as genetic gain per generation (the differencesbetween Ā dan ) divided by generation interval. Heritabilities for milk fat percentage (FP), milk fatyield (FY), milk protein percentage (PP) and milk protein yield (PY) were 0.46, 0.30, 0.28 and 0.17,respectively. A significant increase (P=0.025) in the total milk yield (TMY) from the first generation(G1) to the second generation (G2) resulted in a high significant decrease in the FP (P=0.004). Geneticgains of TMY, FP and PP were 9.76 kg, -0.04% and -0.01% per year, respectively. It is concluded thatselection for higher TMY only negatively affect FP and PP. Selection can be applied based on FY to avoid the decrease of FP. Negative effects of genetic-environmental interaction resulted in slowergenetic gain because the imported cows needed time to adapt to the local environment.